Application of the Finite State Machine Algorithm on 2D Platformer Rabbit Games vs Zombies - Ade Solihin; Eka Wahyu Hidayat; Aldy Putra Aldya (JOIN (Jurnal Online Informatika), 2019)
This research develops Android games by applying the FSM Algorithm (Finite State Machine) for the movement of NPC (Non-Player Character) to produce dynamic movements. The popular and legendary game with the appearance of side scroller is Super Mario Bross and Shovel Knight, the game is the most preferred game of its time to the present, but the game does not apply AI (Artificial Intelligence) so the game seems less challenging. The game is a concept game that is currently rarely used. Based on this, a side scroller-based survival game was created by implementing AI on NPCs on the Android platform. The AI used is the FSM Algorithm which functions to regulate enemy movements. The method used in developing multimedia products of this game uses MDLC (Multimedia Development Life Cycle). Based on the tests that have been carried out, the alpha test results are functionally appropriate and the results of beta testing using UserAcceptence Test (UAT) obtained a value of 86.40% which is declared feasible to use and can be developed. The advantages of this game are the presence of shock elements in the form of landslides, bursts of water, rock rain, and attacks by eagles